Making pulses affordable again: Policy options from the farm to retail in India - Joshi, Pramod Kumar; Kishore, Avinash; Roy, Devesh (International Food Policy Research Institute, 2016)
Rising prices and declining consumption of pulses cause concern in terms of both nutrition and food inflation in India. This paper outlines policy strategies to increase the availability of pulses at affordable prices in India and also points out limitations of some of the most common recommendations for achieving these objectives. There seems to be no option but to increase domestic production of pulses in India. The global supply of pulses is limited compared with India’s needs, and sizable imports by India are bound to increase world prices. Domestic production of pulses in India is most likely piecewise inelastic, meaning that small price increases do not translate into a significant supply response. Because farmers face both production and marketing risks, they increase pulse area and intensify production only when there is a large increase in expected prices that covers the risk premium. Droughts, too, are a major risk for pulses. Access to one or two protective irrigations during the growing season can possibly lead to sizable increases in pulse production and reduce the production risk. The har khet ko paani (assured irrigation) initiative under the Pradhan Mantri Krishi Sinchayee Yojana (PMKSY) program should give priority to pulse-producing areas. The minimum support price (MSP) for pulses, without direct government procurement, helps traders more than farmers because it acts as a focal point for tacit collusion among traders. Farmers will benefit from the MSP only if it is raised substantially from its current levels. The increase in farmgate prices due to a higher MSP will not necessarily lead to an increase in the retail price of pulses because much of the wedge between farmgate prices and consumer prices is traders’ margin. Including subsidized pulses in public distribution systems can save households some money, but it has only a small effect on total consumption of pulses and almost no effect on total protein intake. We suggest, as more potent solutions, investing in research and extension for pulses, aggregating pulse growers into farmer producer organizations, and paying pulse growers or pulse-growing areas for the ecosystem services offered by pulses.